Public Health and International Obligations of States: The Case of COVID-19 on Cruise Ships - Chenhong Liu (MDPI AG, 2021)
Against the backdrop of the COVID-19 outbreak onboard the cruise ship Diamond Princess, both the flag State and the port State should act according to international obligations during the sailing stage, quarantine period after ships’ berthing, and the time when the quarantine period expires. However, the potential danger of the absence of a “genuine link” between the cruise shipowners and the flag State, the lack of coordination of jurisdiction in different sea areas and between different States, and also the lack of special or systematic regulations for infection prevention and control (IPC) at sea and for cruise ships increase the risk of a State’s breach of international obligations. Therefore, it is deemed necessary to improve the responsive measures in international law. This paper, after review and analysis, sheds light on various recommendations on how to improve the responsive measures in international law, including (i) strengthening of the jurisdiction of the flag State, (ii) establishment of a special international cooperation mechanism with an alliance between the WHO and the IMO, and (iii) construction of an IPC mechanism for home ports of cruise ships.